Effect of renal insufficiency and diabetes mellitus on in-hospital mortality after acute coronary syndromes treated with primary PCI. Results from the ALKK PCI Registry. (1st October 2019) - Liosis, Spyridon; Hochadel, Matthias; Darius, Harald; Behrens, Steffen; Mudra, Harald; Lauer, Bernward; Elsässer, Albrecht; Gitt, Anselm K.; Zahn, Ralf; Zeymer, Uwe; ,
Abstract: Background: It is known that patients with acute coronary syndromes (ACS) and diabetes mellitus (DM) are at higher risk for in-hospital adverse events. However, we hypothesized that the higher event rate is due to the patients' subgroup with renal failure (RF), a common sequel of DM. Methods and results: We used data of the prospective ALKK-PCI registry including all consecutive percutaneous coronary interventions (PCI) for ACS of 48 hospitals between 2008 and 2013. We divided 69, 651 patients in four groups according to their history of DM and RF (GFR < 60 ml/min). All-cause, in-hospital mortality of the following four groups: noDM/noRF, DM/noRF, DM/RF, RF/noDM, was: 3.5%, 6.6%, 21.9%, and 14.1% for STEMI and 1.5%, 2.1%, 7.2%, and 5.4% for NSTE-ACS. In a multivariate analysis we looked for independent mortality-predictors. Odds ratios with confidence intervals for the following variables: DM without RF, DM with RF, RF without DM were: 1.62 (1.37–1.90), 3.02 (2.43–3.76), and 2.13 (1.80–2.52) for STEMI and 1.20 (0.99–1.45), 2.72 (2.18–3.88), and 2.08 (1.69–2.56) for NSTE-ACS. We also calculated mortality in four groups (60–90, 45–60, 45–30, <30 ml/min) according to the estimated glomerular filtration rate (eGFR). Mortality rates were: 5.0%, 12.8%, 17.7%, and 31.5% for STEMI and 2.1%, 3.8%, 7.1%, and 12.0% for NSTE-ACS ( p for trend <0.0001 for both). Conclusions: In-hospital death after PCI in patients with ACS and DM is mainly observed in the subgroup with co-existing RF. In a multivariate analysis, DM without RF was a significant mortality-predictor in STEMI, but not in NSTE-ACS. RF, irrespective of co-existent DM, was a stronger predictor than DM alone for both ACS-types (OR > 3) and mortality increased with decreasing eGFR. Highlights: DM and RF are predictors of in-hospital adverse events after recanalization for ACS. Patients with RF had higher event rates regardless of their diabetic state. High event rates in diabetics are driven by those with RF. RF predicted short term mortality better than DM.